Resistance to silver scurf in wild potato species - Zoteyeva, Nadezhda M (MTT, 2007)
Silver scurf caused by Helminthosporium solani Dur. et Mont. has been observed in Northwestern Russia from year to year, but from mid of 90th the amount of the affect of this disease on potato increased. To decrease disease development in potato fields the incorporation of resistance into improved cultivars from highly resistant genotypes is a one of the most promising strategies. Wild potato species is a good source of resistance genes to a large amount of diseases. In order to identify potato wild species which are resistant to silver scurf three year observation of tuber had been conducted. Vegetative seasons with higher temperatures are characterized by more intensive disease development. Disease symptom development on tubers of the same accessions varied in intensity depending on year (LSD = 1,32). During full period of evaluation of large wild potato species (50) and their accession (352) number, the tubers of only individual accesions were symptom free. Such accessions were found within the following species: S. cardiophyllum (2 accessions), S. chancayense (1 accession), S. jamesii (1 accession), S. pinnatisectum Dun. (1 accession), S. stenophyllidium (1 accession) and S. tarijense (1 accession). During three year observation tubers with weak disease symptoms were noted into part of: S. arnezii, S. brachistotrichum, S. cardiophyllum, S. chacoense, S. commersonii, S. famatinae, S. fendleri, S. gibberulosum, S. gourlayi, S. incamayoense, S. jamesii, S. leptostigma, S. kurtzianum, S. maculae, S. papita, S. pinnatisectum, S. piuranum, S. polytrichon, S. spegazzinii, S. stenophyllidium, S. stoloniferum, S. sucrense, S. tarijense, S. toralapanum, S. venturii and S. vernei accessions. Large shares of the accessions with weak disease development were found within the species: S. cardiophyllum (14 of 25 evaluated), S. famatinae (3 of 3), S. jamesii (11 of 19), S. megistacrolobum (4 of 6), S. spegazzinii (8 of 29). The polymorphism for resistance to Phytophthora infestans is present in majority of wild potatoes is also their characteristics for resistance to H. solani. As highly polymorphic for resistance to silver scurf the following species: S. chacoense, S. fendleri, S. hjertingii, S. jamesii, S. kurtzianum, S. pinnatisectum, S. polytrichon and S. spegazzinii were identified. The majority of wild potatoes are considered to be polymorphic for resistance to Phytophthora infestans (Zoteyeva, 1986, 2006). The accession distribution within the species and within the accessions by resistance levels indicates intra specific and intra population polymorphism for resistance to H. solani too.
Keywords: Ka